Marcadores sintáticos no reconto oral de escolares disléxicos - de Souza Batista Kida, Adriana [UNESP]; de ávila, Clara Regina Brandão; Capellini, Simone Aparecida [UNESP] (FapUNIFESP (SciELO), 2015)
Purposes: To investigate, in the oral retelling after reading process, the syntactic markers capable of characterizing different clinical groups of developmental reading disabilities. Methods: Thirty-two Brazilian students were evaluated: dyslexic group (DG) - 16 individuals were diagnosed with developmental dyslexia; control group (CG) - 16 individuals did not present reading difficulties when compared with the DG by age, gender, and educational level. They all read one narrative and one expository text and orally retold what was read. The retellings were recorded, transcribed, and analyzed via Coh-Metrix-Port. The performances were statistically analyzed using productivity indexes, lexical diversity, grammar skills, and complexity. Results: DG showed a lower average of correct sentences in the narrative and expository retellings, fewer words per sentence, and a lower incidence of content words in the expository retelling. Conclusion: The analysis of the microstructure of retellings differentiated the groups' performances. Dyslexic students presented lower grammar skills for narrative and expository text retellings. Fewer words per sentence and a lower incidence of content words characterized the retellings of expository texts by dyslexic students, possibly a consequence of a higher cognitive demand to the reading comprehension of this type of text.
Syntactic markers in the oral retelling of dyslexic students
Keywords: Dyslexia; Evaluation; Learning; Reading